Wielokulturowe estetyki w dyskursie publicznym w Polsce. Próba postkolonialnej interpretacji - Popow, Monika (Kultura-Społeczeństwo-Edukacja, 2015)
The aim of my paper is to present the concept of postcolonial aesthetics, as well as to analyse the phenomena of multicultural aesthetics in public discourse in Poland. In my work the sociological perspective is accompanied with pedagogical one. I point out that aesthetics may be considered as space for identity formation. While analysing multicultural aesthetics in Polish public discourse, I focus on several phenomena. First, I describe invisibility of multicultural aesthetics in art discourse, as well as in educational discourse, and analyse the representations of multicultural aesthetics. I reconstruct the discourse of superiority of The Global North civilisation, and a parallel discourse of primitivism of the Global South. Next, I describe the proces ses of commercialisation and folklorization of multicultural aesthetics occurring in public sphere, especially in mass culture. Finally I reconstruct types of identities formed in the analysed material. The papers concludes with reference to Edward Said's demand for a constant critical reading o f culture.